Analisis Perbandingan Kinerja Keuangan UMKM Pengusaha Kena Pajak dengan UMKM Non Pengusaha Kena Pajak - Arifin, Zaenal; Jati, I Ketut (E-Jurnal Akuntansi, 2022)
This study aims to compare the financial performance of MSMEs for Taxable Entrepreneurs and MSMEs for Non-Taxable Entrepreneurs for the 2017-2019 period by using several financial ratios. The design of this research is comparative descriptive. Sampling used double sampling technique, namely quota sampling and purposive sampling. So that the resulting number of samples is 10 MSMEs of Taxable Entrepreneurs and 10 MSMEs of Non-Taxable Entrepreneurs with a total of 30 MSMEs of Taxable Entrepreneurs and 30 MSMEs of Non-Taxable Entrepreneurs. The method of data analysis in this study is descriptive analysis to determine the average performance of SMEs and hypothesis testing with independent sample t-test. The results of this study indicate that MSMEs of Taxable Entrepreneurs have better performance and have differences based on the ratio of Gross Profit Margin and Return on Assets, while in the Inventory Turnover ratio there is no difference between MSMEs of Taxable Entrepreneurs and MSMEs of Non-Taxable Entrepreneurs. Keywords: Financial Performance; MSME; Taxable Entrepreneur.